1981
DOI: 10.1159/000123126
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptors in the Posterior Pituitary Gland

Abstract: The characteristics of atropine-sensitive binding of l-[3H]-quinuclidinyl benzilate ([3H]-QNB) to membrane re-suspensions of sheep posterior pituitary indicate that the binding sites represent muscarinic cholinergic receptors. Scat-chard plots of 6 saturation experiments showed a single class of binding sites, with an equilibrium dissociation constant of 16 ± 2 pM and a density equivalent to 1.8 ± 0.2 pmol/g wet weight of tissue. Kinetic analysis of 2 association and 3 dissociation curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The observation that this effect is blocked by atropine is consistent with the recent demonstration of specific mus carinic receptors in the neurointermediate lobe of both sheep and rats [36], It also confirms the report by Gosbee and Lederis [13] that direct injection of acetylcholine or carbachol into the neurohypophysis of water-loaded rats in vivo was followed by an apparent increase in VP release. Carbachol is a cholinergic-like agent which has more mus carinic than nicotinic activity [22],…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observation that this effect is blocked by atropine is consistent with the recent demonstration of specific mus carinic receptors in the neurointermediate lobe of both sheep and rats [36], It also confirms the report by Gosbee and Lederis [13] that direct injection of acetylcholine or carbachol into the neurohypophysis of water-loaded rats in vivo was followed by an apparent increase in VP release. Carbachol is a cholinergic-like agent which has more mus carinic than nicotinic activity [22],…”
Section: Discussionsupporting
confidence: 91%
“…choline acetyltransferase [12,16,19] and acetylcholinesterase [39], respectively. Specific muscarinic cholinergic binding sites have also been demon strated in the neurointermediate lobe [36]. In contrast to re…”
mentioning
confidence: 99%
“…Only autoradiographic studies on the intact gland combined with binding studies on isolated cells can fully resolve this problem. The only evidence to date for pituitary muscarinic receptors is that of quisnuclididinyl-benzilate binding sites in the neurointermediate lobe of the rat (Tolliver, Taylor & Burt, 1981;Gregg, 1985) and pirenzepine-sensitive secretory responses to ACh in the frog (Louiset et al 1989). To our knowledge there are no conclusive reports of ligand binding studies aimed at detecting either nicotinic or muscarinic receptors on either freshly dispersed or cultured cells.…”
Section: Cholinergic Excitation Of Central Originmentioning
confidence: 99%
“…Earlier studies demonstrated the presence of specific QNB binding sites in anterior and posterior pituitary of rat and sheep [2,8,12,16,19]. When tissue homogenates were used in these experiments, it was found that the anterior pi tuitary bound approximately 2-3 times as much QN B as the posterior pituitary.…”
Section: Discussionmentioning
confidence: 88%
“…Direct effects could result from ACh traveling in the portal circulation from the median eminence to the pituitary or from ACh re leased from nerve endings in the pituitary. While ACh is present in the median eminence [9] and all lobes of the pitui tary [1], choline acetyltransferase (ChAT), a specific marker for cholinergic neurons [10], is localized in the median emi nence [3,9] [2,8,12,16,19], Most of these reports indicate that the anterior lobe contains more muscarinic receptors than the posterior pituitary. The present investigation utilized an autoradiographic technique to provide a more detailed lo calization of muscarinic receptors in the rat pituitary.…”
mentioning
confidence: 99%